Pengaruh Penjualan dan Beban Pajak Penghasilan Terhadap Laba Bersih Perusahaan Sub Sektor Perkebunan yang Terdaftar di BEI - Putri Hadiyanti Pratiwi; Novi Khoiriawati (Ekonomis: Journal of Economics and Business, 2023)
The plantation sector is the economy's backbone and the state's foundation. The plantation sector contributed IDR 429 trillion to the national Gross Domestic Product (GDP) in 2016. Oil palm, as the main plantation product in Indonesia, has a high economic value compared to other plantation products and is one of the primary sources of the country's foreign exchange. The increase in local demand is one of the main factors influencing the high production of palm oil. However, the increase in palm oil production is inversely proportional to the company's net profit increase. This research aims to determine the effect of sales and tax expenses on the net profit of plantation sub-sector companies listed on the IDX. This research uses secondary data from the Indonesia Stock Exchange website. The population in this study were 25 companies in the plantation sub-sector listed on the IDX but only used 21 selected companies as research samples with four years of observation. The financial data is the annual financial reports from 2018 to 2021. The results show no significant effect between sales and net profit. Meanwhile, income tax expense has a significant effect on net income partially. Sales and income tax expenses together affect net income simultaneously.